2020
DOI: 10.1016/j.cub.2020.04.001
|View full text |Cite|
|
Sign up to set email alerts
|

Neural Correlates of Body Integrity Dysphoria

Abstract: Highlights d Target limb sensorimotor area shows a breakdown of the functional connectivity d Left premotor cortex typically involved in limb multimodal integration is atrophic d Right parietal area representing body shape is structurally and functionally altered d Atrophy in this right parietal area correlates with simulation of being an amputee

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
80
2

Year Published

2021
2021
2025
2025

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 41 publications
(96 citation statements)
references
References 37 publications
(66 reference statements)
12
80
2
Order By: Relevance
“…Futhermore, limb disuse has been shown to be accompanied by reduced neural activity in the corresponding primary motor cortex (Gandola et al, 2017). In accordance with these findings, we recently showed a negative correlation between pretending and the concentration of gray matter in the right superior parietal lobule (Saetta et al, 2020b), a key node for both motor execution and motor imagery networks (Solodkin et al, 2004). Along these lines, we showed that BID individuals in their pretending state were biased towards the more visually guided perception on the LAMP task.…”
Section: Discussion Study IIsupporting
confidence: 83%
See 2 more Smart Citations
“…Futhermore, limb disuse has been shown to be accompanied by reduced neural activity in the corresponding primary motor cortex (Gandola et al, 2017). In accordance with these findings, we recently showed a negative correlation between pretending and the concentration of gray matter in the right superior parietal lobule (Saetta et al, 2020b), a key node for both motor execution and motor imagery networks (Solodkin et al, 2004). Along these lines, we showed that BID individuals in their pretending state were biased towards the more visually guided perception on the LAMP task.…”
Section: Discussion Study IIsupporting
confidence: 83%
“…Ten individuals with BID were recruited through online forums or personal contacts established in previous studies (Saetta et al, 2020b) (Males: 8, Females: 2, Right-sided amputation desire: 7, Left-sided amputation desire: 3, Mean age = 41.00 years, SD = 12.36). The desire for amputation was assessed using the Zurich Xenomelia Scale (Aoyama et al, 2012).…”
Section: Studymentioning
confidence: 99%
See 1 more Smart Citation
“…First, while BID likely develops in childhood and may be related to amputation-related experiences ( Barrow and Oyebode, 2019 ), SPP is an acquired condition in response to brain damage, typically of the right hemisphere, that typically also causes contralateral left limb paralysis. Moreover, while BID individuals recognize the unwanted limb as part of their current but undesired body, SPP is a disownership disorder, primarily characterized by a positive component, reflecting a “distorted mental representation of reality” ( Bottini et al, 2009 , p. 589), that is the delusional misattribution of the paralyzed limb to someone else ( Gerstmann, 1942 ; Romano et al, 2014 ; Saetta et al, 2020 ). Another related clinical condition is asomatognosia, which is caused by a similar (more often a right lateral) cerebral lesion as SPP.…”
Section: Characteristics and Etiology Of Bidmentioning
confidence: 99%
“…Major characteristics observed in the amputation variant of BID include (1) dysphoric feelings about a normal body morphology and/or functionality originating from a mismatch between the mental body image, i.e., the conscious representation of body size and shape, and the perceived body ( Saetta et al, 2020 ), (2) lack of ownership over a limb, (3) excessive attention devoted to the limb, and (4) intact insight regarding the condition and its unusual nature ( Giummarra et al, 2011 ). Initial studies on BID have shown that in the case of a desire for amputation, most patients with BID desired amputation of either a left-sided limb or both limbs ( First, 2005 ).…”
Section: Characteristics and Etiology Of Bidmentioning
confidence: 99%